2010
DOI: 10.1016/j.susc.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Misfit-dislocation-mediated heteroepitaxial island diffusion

Abstract: Scanning tunneling microscopy combined with molecular dynamics simulations reveal a dislocation-mediated island diffusion mechanism for Cu on Ag(111), a highly mismatched system. Cluster motion is tracked with atomic precision at multiple temperatures and diffusion barriers and prefactors are determined from direct measurements of hop rates. The nonmonotonic size dependence of the diffusion barrier is in good agreement with simulations and can lead to enhanced mass transport upon coarsening, in surprising cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Using low-temperature scanning tunneling microscopy (STM), we have previously shown that larger clusters have surprisingly low diffusion barriers and a novel dislocation mechanism that is related to the ~12% lattice mismatch for Cu on Ag(111) [25,26]. Here, we show that Cu trimers diffuse large distances following their formation.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Using low-temperature scanning tunneling microscopy (STM), we have previously shown that larger clusters have surprisingly low diffusion barriers and a novel dislocation mechanism that is related to the ~12% lattice mismatch for Cu on Ag(111) [25,26]. Here, we show that Cu trimers diffuse large distances following their formation.…”
Section: Introductionmentioning
confidence: 62%
“…The extremely low diffusion barrier for the linear trimer, combined with the preference for this structure during nucleation, make the trimer an extremely important contributor to mass transport for Cu on Ag(111). The effects of lattice mismatch are manifest in the observed directions of hopping and rotation that require intermediate steps involving trimers of mixed fcc-hcp character that shorten Cu-Cu bonds to relieve strain, in a one-dimensional analog of the misfit-dislocation mechanism responsible for the low diffusion barriers of larger Cu clusters on Ag(111) [25,26]. Because the novel diffusion phenomena for both small and large clusters of Cu on Ag(111) result from lattice mismatch, it is likely that similar behavior will occur in other heteroepitaxial systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For even larger sizes, other mechanisms may come into play, such as vacancy diffusion inside the islands [46]. Finally, in heteroepitaxial systems where lattice mismatch also participates in the total energy, the formation of misfit dislocations within the islands represents another significant contribution to consider [47,48].…”
Section: Introductionmentioning
confidence: 99%